Enhancing students' mathematical problem-solving proficiency: A synergistic approach of the bar model and butterfly method - Buttrama, Supaporn; Yonwilad, Wannatida (Journal of Green Learning, 2023)
The objective of this study is to enhance students' mathematical problem-solving by using a synergistic approach employing the bar model and butterfly method. The sample for this study was 62 seventh-grade students from Kantho Wittayakarn school in Tha Kantho district, Kalasin province during the first semester of the academic year 2022. The research tools consisted of  learning management strategy using the bar model and the butterfly method, test for fractal problem solving, and  interviewing form for learning activities using the bar model and the butterfly method. The study consistently demonstrated a noteworthy enhancement in seventh-grade students' mathematical problem-solving, particularly in the after-school sessions. Statistical analysis revealed a significant increase in learning achievement levels, surpassing the performance observed before school, with a statistical significance level of .05. The findings consistently suggest that the utilization of the bar model and butterfly method within a learning cycle model can serve as a reliable and effective alternative for advancing students' comprehension of mathematical concepts. The results underscore the consistent positive impact of this synergistic instructional approach on students' mathematical problem-solving.